PENGARUH PEMBERIAN SEDUHAN DAUN KELOR TERHADAP KUANTITAS AIR SUSU IBU (ASI) PADA IBU MENYUSUI BAYI 0-6 BULAN DI WILAYAH KERJA PUSKESMAS SUMUR BATU KOTA BANDAR LAMPUNG - Eka Trismiyana; Mei Kurnia Pitaloka (Malahayati Nursing Journal, 2020)
THE EFFECT OF GIVING KELOR LEAVES TOWARDS MILK (ASI) WATER QUANTITY IN 0-6 MONTHS OF BABY BREAST MILK IN WORKING AREAS OF HEALTH CENTER OF BATU BANDAR LAMPUNG CITY IN 2019 Introduction: Bandar Lampung City Health Office data shows that there are 3 Puskesmas with the lowest ASI coverage, namely Sumur Batu Health Center, with a total of 6 months exclusive breastfeeding coverage 142, as many as 102 infants (28.17%) did not receive exclusive breastfeeding at 6 months of age, and 40 ASI received exclusive breastfeeding, Way Kandis Health Center, with a total of 6 months exclusive breastfeeding coverage in 919, 621 infants (32.93%) did not receive exclusive breastfeeding aged 6 months, and 298 ASIs received exclusive breastfeeding, Kemiling Health Center, with total breastfeeding coverage exclusive 6 months 98, 62 babies (36.73%) did not get exclusive breastfeeding at the age of 6 months, and 36 ASIs received exclusive breastfeeding (Data from Bandar Lampung City Health Office, 2018). Objective: To determine the effect of administration of Moringa leaves on the quantity of breast milk in breastfeeding mothers of infants 0-6 months in the Work Area of Sumur Batu Health Center, Bandar Lampung City in 2019.Method: This type of research is quantitative. The design of the Quasi Experimental method is one group pretest-posttest one group pretest-posttest approach. Population and sample of 30 people. Data analysis uses univariate and bivariate with t-test.Results: The average quantity of breast milk in breastfeeding mothers of infants 0-6 months before being given moringa leaf steeping in the Sumur Batu Health Center Working Area, with a mean of 72.50 standard deviation 25.317 standard error 4.622, after being given steeping leaves of moringa mean 97.17 standard deviation of 17.601 standard error 3.214. P-value 0,000 (0.05) t-test test results.Conclusion: means that there is an effect of steeping Moringa leaves on the quantity of breast milk in breastfeeding mothers of infants 0-6 months in the Sumur Batu Community Health Center Working Area in Bandar Lampung City in 2019. Suggestions for respondents are expected to be used as input for clients in order to know how to increase the smoothness of breast milk during breastfeeding. Keywords: Moringa Leaf Steeping, Breast Milk, Breastfeeding Mother  INTISARI: PENGARUH PEMBERIAN SEDUHAN DAUN KELOR TERHADAP KUANTITAS AIR SUSU IBU (ASI) PADA IBU MENYUSUI BAYI 0-6 BULAN DI WILAYAH KERJA PUSKESMAS SUMUR BATU KOTA BANDAR LAMPUNG TAHUN 2019 Pendahuluan: Data Dinas Kesehatan Kota Bandar Lampung menunjukan  bahwa terdapat 3 Puskesmas dengan cakupan pemberian ASI terendah yaitu, Puskesmas Sumur Batu, dengan total keseluruhan cakupan ASI eksklusif 6 bulan 142, sebanyak 102 bayi (28.17%) tidak mendapat ASI eksklusif usia 6 bulan, dan 40 ASI mendapat ASI eksklusif, Puskesmas Way Kandis, dengan total keseluruhan cakupan ASI eksklusif 6 bulan 919, sebanyak 621 bayi (32.93%) tidak mendapat ASI eksklusif usia 6 bulan, dan 298 ASI mendapat ASI eksklusif, Puskesmas Kemiling, dengan total keseluruhan cakupan ASI eksklusif 6 bulan 98, sebanyak 62 bayi (36.73%) tidak mendapat ASI eksklusif usia 6 bulan, dan 36 ASI mendapat ASI eksklusif (Data Dinkes Kota Bandar Lampung, 2018).Tujuan: Untuk mengetahui pengaruh pemberian seduhan daun kelor terhadap kuantitas air susu ibu (ASI) pada ibu menyusui bayi 0-6 bulan di Wilayah Kerja Puskesmas Sumur Batu Kota Bandar Lampung tahun 2019.Metode: Jenis penelitian ini adalah Kuantitatif. Desain penelitian metode Quasi Eksperimental pendekatan one group pretes-postes one group pretes-postes. Populasi dan sampel 30 orang. Analisa data mengguanakan univariat dan bivariate dengan t-tes.Hasil : Rata-rata kuantitas air susu ibu (ASI) pada ibu menyusui bayi 0-6 bulan sebelum diberi seduhan daun kelor di Wilayah Kerja Puskesmas Sumur Batu, dengan mean 72,50 standar deviasi 25,317  standar eror 4,622, setelah diberi seduhan daun kelor mean 97,17 standar deviasi 17,601  standar eror 3,214. Hasil uji t-tes p-value 0.000 (0.05).Kesimpulan : artinya terdapat pengaruh pemberian seduhan daun kelor terhadap kuantitas air susu ibu (ASI) pada ibu menyusui bayi 0-6 bulan di Wilayah Kerja Puskesmas Sumur Batu Kota Bandar Lampung Tahun 2019. Saran bagi responden diharapkan hasil penelitian ini dapat digunakan sebagai masukan bagi klien agar dapat mengetahui bagaimana cara menambah kelancaran ASI pada masa menyusui. Kata Kunci             : Seduhan Daun Kelor, ASI, Ibu Menyusui